Gender Inequality and Domestic Violence in Lampung Province: Mubadalah as a Solution - Suwondo (Brajamusti Publication, 2025)
Gender inequality is the structural root of domestic violence (DV) which is still rampant in various regions, including Lampung Province. This article aims to reveal the relationship between gender inequality and the high rate of violence against wives, and to analyze how the Mubadalah approach can be an alternative solution in preventing domestic violence. This study uses a qualitative approach with a case study in Mesuji Regency, Lampung, which has a high prevalence of domestic violence cases. Data were obtained through in-depth interviews, participatory observation, and documentation studies. The Mubadalah theory developed by Faqihuddin Abdul Kodir was used as an analytical tool, with an emphasis on the principle of mutuality and justice in husband-wife relations. The results of the study show that violence against wives does not only stem from economic imbalance and social pressure, but is also influenced by religious interpretations that are patriarchal in nature. The Mubadalah approach offers a reinterpretation of Islamic values ​​that are more gender-just, so that it can be a transformative strategy in building equal and violence-free household relations. This article recommends mainstreaming Mubadalah values ​​in religious education, family policies, and domestic violence victim assistance programs at the local level